ANALISIS PERBANDINGAN NILAI DERAJAT KEJENUHAN MENGGUNAKAN MODEL GREENSHIELD, GREENBERG DAN UNDERWOOD TERHADAP MKJI 1997 PADA JALAN PERKOTAAN TIPE 2/2 UD (STUDI KASUS RUAS JALAN SALEH SUNGKAR AMPENAN KOTA MATARAM) - ROHANI ROHANI; HASYIM HASYIM (Universitas Mahasaraswati K. Mataram, 2023)
If the population increases and the total traffic flow also increases without being matched by an adequate increase and improvement of road infrastructure, it will result in an increase in the degree of saturation which is a parameter in determining the performance of a road section. One of the roads affected by the population growth is the Saleh Sungkar road which is an urban road type 2/2 UD. The Greenshield, Greenberg and Underwood models are the 3 models used to determine the relationship between volume (flow), speed (speed) and density (density). The relationship between flow, speed and density is used to determine or determine the mathematical value of the capacity of a road section and the degree of saturation. This study aims to determine the comparison of the degree of saturation of Jalan Saleh Sungkar which is an urban road using the Greenshield, Greenberg and Underwood models against MKJI 1997. From the results of the analysis, it was obtained that the degree of saturation using the Indonesian Road Capacity Manual (MKJI 1997) was 0.53, so Jalan Saleh Sungkar was at the level of sevice